Team Toyota : transplanting the Toyota culture to the Camry plant in Kentucky - Besser, Terry L., 1945- (SUNY series in the sociology of work., 1996)
In Team Toyota Besser presents the results of an in-depth study of Toyota's assembly plant in Georgetown, Kentucky. Based on employee interviews, analyses of company publications, newspaper accounts, interaction with company employees and attendance at company events over a five-year period, this book documents how Toyota is replicating its style of management and its team culture in its Kentucky plant. Team Toyota is one of the few books about Japanese organizations that incorporates the perspectives of both nonmanagement and management employees.--